THE INFLUENCE OF EYE COORDINATION AND SHOULDER JOINT FLEXIBILITY ON SHOOTING ACCURACY IN THE AIR OF HANDBALL ATHLETES - Kurniawan , Dwi Indra; Sukriadi, Slamet; Arif , Muhamad; Nasution, Harry Syahputra (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The game of handball is a sports game, just like sports games such as football, basketball and others. Because this game relies on almost all physical components such as Strength, Speed, Endurance, Flexibility and Coordination. This research will use eye-hand coordination, namely the total score achieved by the testee in assembling and combining efficient eye and hand movements by carrying out the test with a hand and aye coordination tool